LIBRARIAN PERFORMANCE IN SERVICES AT THE REGIONAL LIBRARY AND ARCHIVES SERVICE OF TOJO UNA-UNA REGENCY - Triani, Nenny; Hattab, Syahruddin; Nuraisyah, Nuraisyah (Penerbit Lafadz Jaya, 2025)
Research related to Librarian Performance in Services at the Regional Library and Archives Service of Tojo Una-Una Regency, aims to analyze the performance of librarians and explain the inhibiting factors of librarian performance in services. The research method used is qualitative with data collection methods in the form of interviews, observations and documentation. However, when viewed from the performance indicators based on Sedarmayanti's theory, there are still inhibiting factors for Librarian Performance in Services at the Regional Library and Archives Service of Tojo Una-Una Regency, namely the lack of competence and initiative of librarians at the Regional Library and Archives Service of Tojo Una-Una Regency, causing an imbalance in the services received by library visitors so that it affects the quality of the performance produced. In the context of Punctuality and communication of library service officers are effective in providing services.